Positive impact analysis of kasti traditional games on social interactions of elementary school - Dewi Anggraini; Aan Widiyono; Abdullah Efendi (Journal Of Sport Education (JOPE), 2023)
(English)The aim of this research is to determine the positive impact of the traditional game of kasti on the social interactions of students at SDN 4 Kedungcino. The type of research used is qualitative research using observation, interviews and documentation methods. The research sources consisted of sports teachers and student representatives from SDN 4 Kedungcino. Checking the validity of data with credibility, transferability, dependability and confirmability. Data analysis techniques use data reduction, data presentation and verification conclusions. Based on the results of the researcher's analysis, it can be said that the traditional game of Kasti has a positive impact on students, therefore the traditional game of Kasti must be preserved and cultivated among children today. (Indonesian)Tujuan dari penelitian ini yaitu untuk mengetahui dampak positif dari permainan tradisional kasti pada interaksi sosial siswa SDN 4 Kedungcino. Jenis penelitian yang di gunakan adalah penelitian kualitatif dengan menggunakan metode observasi, wawancara dan dokumentasi. Narasumber penelitian terdiri dari guru olahraga dan perwakilan siswa SDN 4 kedungcino. Pemeriksaan keabsahan data dengan kredibilitas, transferabilitas, dependabilitas dan konfirmanbilitas. Teknik analisis data menggunakan reduksi data, penyajian data dan kesimpulan verifikasi. Berdasarkan hasil analisis peneliti, dapat dikatakan bahwa permainan tradisional kasti memiliki dampak positif pada siswa, maka dari itu permainan tradisional kasti harus tetap dilestarikan dan dibudayakan kepada anak-anak pada zaman sekarang.Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.